Elements of Father Andrei Scrima's Ecumenical Activity as Reflected in File No. 0005468 from the "Securitate" Archives - Morariu, Maxim (Review of ecumenical studies, 2020)
The Romanian Archimandrite Andrei Scrima was an important worldwide theological personality. His activity as a kind of ambassador of the Ecumenical Patriarch Athenagoras to the Second Vatican Council, together with his publications, conferences and activity as a professor, transformed him into a voice that was almost always trusted. His attitudes and speeches that criticized the Romanian Communist regime made him also to be seen as an enemy by Bucharest's government. In this context, the Securitate was interested in his ecumenical activity and in his ideas regarding the ecumenism and the potential role of the Romanian Orthodox Church there, trying also to see if his theological ideas were related to the political world and contained criticisms of the dictatorial regime or its relationship with the Church. In this paper, we will describe how his ecumenical activity is described in the Securitate Archives. Due to the fact that file no. 00005468 contains the most important information regarding this topic, the main references cited in the paper are extracted from this source.